PKM EKONOMI HIJAU OLAHAN SAMPAH ORGANIK BERBASIS ECO-ENZYME DI BANK SAMPAH SEKUMPUL MARTAPURA - Anang Kadarsah; Witiyasti Imaningsih; Yanti Fauziah (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Waste management in Sekumpul Urban Village, Martapura, faces serious challenges, where only a quarter of the total 8 tons of daily waste can be properly managed. This is due to limited personnel, low public awareness, and a lack of effective, simple technology implementation. In fact, organic waste has great potential to be processed into economically valuable products such as compost, liquid fertilizer, maggot feed, and eco-enzyme. This community service program (PKM) aims to empower the community of Sekumpul Urban Village by processing organic waste into eco-enzyme-based products with economic value. This creates an integrated solution for both environmental management and improving community welfare. The PKM activities were held at the Sekumpul Waste Bank and involved the integrated participation of students, employees, and waste bank customers. The methods used included socialization, technical training, and program evaluation. Training materials covered waste sorting, compost production, maggot cultivation, and eco-enzyme production to support stingless bee cultivation. The evaluation results showed a remarkable knowledge transformation. Participants' understanding of the green economy concept increased from 7.1% to 100%. Technical knowledge about eco-enzyme production, maggot cultivation, and the stacking bucket method also saw a significant increase. This program successfully created 14 change agents at the community level, who have the potential to develop a green economy based on organic waste processing. These findings highlight the urgency of follow-up programs, such as practical training and continuous assistance, to ensure that the knowledge gained can be implemented into tangible actions.